Improving Extension Program Development Using Audience Segmentation - Paul Monaghan; Laura Warner; Ricky Telg; Tracy Irani (EDIS)
Developing an impactful Extension program depends on acquiring a deep understanding of the audience’s specific needs and preferences. Audience segmentation allows an agent to address the variability among Extension clientele, in order to deliver the programming and messages that are most meaningful to an audience/clientele segment. This 5-page fact sheet was written by Paul Monaghan, Laura Warner, Ricky Telg, and Tracy Irani, and published by the UF Department of Agricultural Education and Communication, November 2014. (UF/IFAS photo Marisol Amador)